Super‐resolution deep imaging with GB‐STED microscopy. Issue 1 (18th November 2015) - Yu, Wentao; Ji, Ziheng; Dong, Dashan; Yang, Xusan; Xiao, Yunfeng; Gong, Qihuang; Xi, Peng; Shi, Kebin
Abstract : A STED based super resolution deep‐imaging modality is reported by utilizing a hollow Bessel beam as depletion and a Gaussian beam as excitation beam. Comparing to the conventional STED microscope, an improvement on lateral resolution at the depth up to ∼150μm inside the specimen is experimentally demonstrated, with ∼100μm depth inside biological phantom. The proposed scheme can find promising applications for deep tissue imaging, laser nano‐fabrication, and dense optical storage with super‐resolution. Abstract: Stimulated emission depletion (STED) microscopy has become a powerful imaging and localized excitation method, breaking the diffraction barrier for improved spatial resolution in cellular imaging, lithography, etc. Because of specimen‐induced aberrations and scattering distortion, it is a great challenge for STED to maintain consistent lateral resolution deep inside specimens. Here we report on deep imaging STED microscopy using a Gaussian beam for excitation and a hollow Bessel beam for depletion (GB‐STED). The proposed scheme shows an improved imaging depth of up to about 155 μm in a solid agarose sample, 115 μm in polydimethylsiloxane, and 100 μm in a phantom of gray matter in brain tissue with consistent super resolution, while standard STED microscopy shows a significantly reduced lateral resolution at the same imaging depth. The results indicate the excellent imaging penetration capability of GB‐STED, paving the way for deep tissue super‐resolution imaging and three‐dimensional precise laser fabrication.